The New Geography Curriculum for Upper Secondary General Education in the Netherlands - Vankan, Leon (Journal of Geography Education, 2005)
The present curriculum for geography in upper secondary general education was introduced in 1998 as a part of a new national curriculum that emphasises active and independent learning, information skills and investigation skills. The focus is on decision making and problem solving about e.g. territories, migration, traffic, region marketing, environment and hazard management. Geographical knowledge is used to analyse these problems. The new curriculum, which will be introduced in 2007, is system oriented and it puts regional geography back into the heart of the school subject. On three levels, the global level, South East Asia and the Dutch national level, region specific problems are elaborated. For instance: the food problem and climate change, cultural diversity, environmental problems and water management. Geographical skills, methods and thinking are as important as in the present curriculum. Geographical understanding is no longer a means. It has become a goal in itself.